2020
DOI: 10.1016/j.psychres.2020.113130
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety, stress levels of physicians and associated factors in Covid-19 pandemics

Abstract: Since January 2020 Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre -including this research content -immediately available in PubMed Central and other publicly funded repositories, such as the WHO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

83
632
26
106

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 635 publications
(847 citation statements)
references
References 11 publications
83
632
26
106
Order By: Relevance
“…Similar to our findings, investigators in China, Italy, and Turkey have reported higher levels of anxiety and depression in female health care providers during the COVID-19 pandemic. 3,[10][11][12][13][14] While investigators in Turkey found that having a child was associated with lower anxiety and depression levels, we did not find a similar protective effect of parenthood or differences in any of the other factors that we examined.…”
Section: Discussioncontrasting
confidence: 85%
“…Similar to our findings, investigators in China, Italy, and Turkey have reported higher levels of anxiety and depression in female health care providers during the COVID-19 pandemic. 3,[10][11][12][13][14] While investigators in Turkey found that having a child was associated with lower anxiety and depression levels, we did not find a similar protective effect of parenthood or differences in any of the other factors that we examined.…”
Section: Discussioncontrasting
confidence: 85%
“…Based on the cross-stressor adaptation hypothesis [ 62 ], exercise might result in the adaptation of the sympathetic nervous system and the hypothalamus–pituitary–adrenal axis [ 49 , 63 , 64 ], which in turn lead to anxiolytic effects. This suggests that frequent exercisers might benefit from anxiolytic effects of exercise, especially during the COVID-19 pandemic [ 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likely those with a more internal locus of control will be more active when using the Internet, but the mental health implications of these are unclear. Finally, we expect greater psychological symptoms among young adults [ 2 , 4 , 8 , 13 , 32 ] and women [ 8 , 11 , 13 , 43 ].…”
Section: Introductionmentioning
confidence: 99%